An experimental and numerical study on quasi-static and dynamic crashing behaviors for tailor rolled blank (TRB) structures. (15th March 2017) - Sun, Guangyong; Zhang, Huile; Lu, Guoxing; Guo, Jianwen; Cui, Junjia; Li, Qing
Abstract: Design for lightweight and crashworthiness remains a fairly challenging issue in vehicle industry. These two performance characteristics often conflict with each other. While tailor rolled blank (TRB) structures, as a relatively newer configuration, are of potential to reduce the weight and improve the crashworthiness simultaneously; unfortunately there have been rare experimental investigations reported in literature for more extensive applications of TRB techniques. This paper aimed to explore the crashworthiness of the TRB top-hat (TRBTH) structures subjected to axial quasi-static/dynamic crash loading experimentally and numerically. First, three representative TRBTH configurations and the corresponding conventional top-hat structures with uniform thickness (THUT) were considered to conduct quasi-static/dynamic axial crashing experiments, respectively. The results revealed that TRBTH exhibited superior crashworthiness to the THUT counterpart with more stable deformation during the crushing process. Second, the finite element (FE) models of the TRBTH and THUT were established and validated experimentally. These FE simulation results agreed well with the testing results. Third, based on the validated FE models, the effects of the thickness distribution and position of transition zone on the crashworthiness of TRBTH were explored; and the results showed that they influenced the crashworthiness of TRBTH significantly. Furthermore, the crashworthiness of the TRBTH and corresponding THUT were compared; and the results indicated that the TRBTH is evidently superior to the conventional THTU in overall crashworthiness for the same weight. Therefore, the TRB technology is definitely effective and feasible for lightweighting design of vehicle, and the study is expected to provide some primary data and technical guidance for lightweight and crashworthiness design of TRB structures. Graphical abstract: Highlights: Three TRBTH and corresponding THUT are conducted quasi-static axial crushing experiments and simulation. Three TRBTH and corresponding THUT are conducted dynamic axial crushing experiments and simulation. Simulation results agreed well with the corresponding test results. The crashworthiness of TRBTH is superior to that of THTU.